1986
DOI: 10.1016/0018-506x(86)90018-8
|View full text |Cite
|
Sign up to set email alerts
|

Prior intrauterine position influences body weight in male and female mice

Abstract: In two longitudinal studies, intrauterine location of male and female Rockland-Swiss mice relative to fetuses of the same and opposite sex dramatically influenced body weight. In one study, body weight of males and females that were located in utero between two female fetuses (OM animals) or between two male fetuses (2M animals) was assessed from birth to the time of weaning (25 days of age). The body weights of 2M females were indistinguishable from those of OM and 2M males on all but a few of the 25 postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…The effect of prenatal testosterone on body mass and growth is not clear. Whereas some studies have found that testosterone during the pre-natal phase retards intra-uterine growth and leads to low birth weight of females [55,56], others have found the opposite result [15,16,57] or none [58]. Given the lack of sexual dimorphism in the rabbit with respect to birth mass and growth, our results are perhaps not surprising [59,6,9].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The effect of prenatal testosterone on body mass and growth is not clear. Whereas some studies have found that testosterone during the pre-natal phase retards intra-uterine growth and leads to low birth weight of females [55,56], others have found the opposite result [15,16,57] or none [58]. Given the lack of sexual dimorphism in the rabbit with respect to birth mass and growth, our results are perhaps not surprising [59,6,9].…”
Section: Discussioncontrasting
confidence: 58%
“…This can have immediate and long-term effects on the morphological, physiological and behavioral development of littermates, including on postnatal body mass and growth [14,10]. In laboratory mice (Mus musculus), for example, young of both sexes located between two male fetuses (2M offspring) have greater postnatal body mass and long-term growth than fetuses with no male neighbors (0M offspring) [15,16]. It is presently unclear, however, whether this depends on a species' degree of sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Male and female oVspring developing adjacent to two siblings of the same sex were heavier than those who shared the incubation environment with two individuals of the opposite sex. EVects of steroid hormone exposure during pregnancy on neonate weight have been repeatedly reported in mammals (Kinsley et al 1986;Petridou et al 1990;Kaijser et al 2000). Among squamate reptiles, manipulative experiments conducted at diVerent postembryonic stages have frequently shown that testosterone inhibits mass gain and skeletal growth (review in , although Uller and Olsson (2003b) reported increased growth of hatchling L. vivipara (live-bearing strain) exposed to exogenous testosterone as embryos.…”
Section: Discussionmentioning
confidence: 96%
“…Fetuses located between two males have increased concentrations of testosterone compared to fetuses located between two females [2], and such fetuses are heavier, suggesting that the intrauterine position may influence metabolic set points involved in the regulation of body weight and fat storage [3]. …”
Section: Introductionmentioning
confidence: 99%